DEMYSTIFYING BAG3 CARDIOMYOPATHY - Yulith Roca Alvarez, MD (Elsevier, 2024)
Therapeutic Area: Heart Failure Case Presentation: A 56-year-old male with progressive exertional dyspnea and ankle edema was evaluated in the cardiology office. The patient had no overt traditional cardiac risk factors. ECG showed sinus rhythm and a right bundle branch block. The echocardiogram showed an LVEF of 45-50% and a severely dilated LV measuring 7.2 cm at end-diastole, with an abnormal global longitudinal strain (GLS) (11.6%) and apical and mid-wall sparing. Ischemic workup was negative. Genetic testing revealed a pathogenic variant in BAG3 (p.Glu471Argfs*95). His father and two siblings were also carriers of the same variant. He was treated with beta-blockers, angiotensin-neprilysin inhibitor, mineralocorticoid receptor antagonist, and an SGLT2 inhibitor. Frequent runs of non-sustained ventricular tachycardia prompted primary prevention implantable cardioverter defibrillator placement. Close follow-up was arranged, given the high risk for deterioration and progressive heart failure. Background: The cause of dilated cardiomyopathy (DCM) can be determined in approximately 40% of cases due to genetic testing now being widely available. BAG3 mutations account for 2-5% of DCM cases; BAG 3 gene encodes a protein crucial for maintaining the structure and function of cardiomyocytes. Mutations in BAG3 disrupt its normal function, leading to myofibrillar disarray and systolic dysfunction. Conclusions: The BAG3 mutation, in this case, resulted in a premature translational stop of the BAG3 gene, disrupting the last 105 amino acids of the BAG3 protein. Inheritance follows an autosomal dominant pattern, and penetrance is 40%. Left ventricular global longitudinal strain (GLS) may inform outcomes beyond LVEF in patients with heart failure and reduced ejection fraction. Currently, preliminary research involving gene therapy in animal models shows that replenishing normal levels of BAG3 may have salutary effects. However, essential questions remain on how it can be implemented effectively in human subjects.